Penerapan Aplikasi Pelayanan Rakyat Online Sebagai Layanan Pengaduan Publik di Diskominfo Kota Denpasar Provinsi Bali - I Dewa Gede Agung Putra Narayana; Ikhlas Amri (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2023)
The author focuses on given the rise of public complaints on social media regarding damaged facilities and infrastructure, inaccurate information, and the phenomenon of natural damage which urgently needs follow-up from the government. Purpose: This study aimed to identify and analyze the online public service application (PRO) as a public complaint service at the Communications and Information Office of Denpasar City, Bali Province. Methods: This study uses a descriptive qualitative method with an inductive approach and an analysis of the e-Government theory from Richardus Eko Indrajit. Data collection techniques use in-depth interviews (5 informants), documentation, and observation. Results/Findings: There is still physical and digital infrastructure in the form of Network System Speed, Servers, Big Data Center Rooms, and Media Centers that need to be improved. Conclusion: This shows that the Denpasar PRO Application has been implemented well, but in its application in the community, is still not fully implemented by the community. Although there are several obstacles, the efforts that have been made by the government in overcoming these obstacles are to organize programmatic outreach activities to the community.